2019
DOI: 10.1080/10872981.2019.1666538
|View full text |Cite
|
Sign up to set email alerts
|

Does online learning work better than offline learning in undergraduate medical education? A systematic review and meta-analysis

Abstract: With the increasing use of technology in education, online learning has become a common teaching method. How effective online learning is for undergraduate medical education remains unknown. This article’s aim is to evaluate whether online learning when compared to offline learning can improve learning outcomes of undergraduate medical students. Five databases and four key journals of medical education were searched using 10 terms and their Boolean combinations during 2000–2017. The extracted articles on under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

25
464
6
34

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 636 publications
(621 citation statements)
references
References 39 publications
25
464
6
34
Order By: Relevance
“…which have also attracted the attention of medical educators. Pei and other scholars [1] conducted a metaanalysis of the literature in 2000-2017, systematically reviewed 3700 articles, selected 16 articles that met the research standards, and discussed the degree of knowledge and skills mastered by online and o ine learning for medical undergraduates. Compared with o ine learning, online learning has advantages in promoting the knowledge and skills of medical undergraduates and is a feasible method.…”
Section: Analysis Of Chinese Dental Professional Coursesmentioning
confidence: 99%
See 1 more Smart Citation
“…which have also attracted the attention of medical educators. Pei and other scholars [1] conducted a metaanalysis of the literature in 2000-2017, systematically reviewed 3700 articles, selected 16 articles that met the research standards, and discussed the degree of knowledge and skills mastered by online and o ine learning for medical undergraduates. Compared with o ine learning, online learning has advantages in promoting the knowledge and skills of medical undergraduates and is a feasible method.…”
Section: Analysis Of Chinese Dental Professional Coursesmentioning
confidence: 99%
“…At the beginning of the New Year in 2020, the coronavirus disease 2019 (COVID-19) outbreak became a global public health incident and has constituted a public health emergency of international concern so far [1] , as a result, the online education has been popularized and developed. The epidemic increased not only the importance and urgency of online education, but also provided an opportunity for an in-depth discussion of online education: For medical colleges and universities, how do teachers and students evaluate online teaching?…”
Section: Introductionmentioning
confidence: 99%
“…Although online CME is relatively new, numerous studies have pointed to its efficacy by evaluating measurements of its effectiveness over time [2][3][4][5][6][7][8]. Moreover, there are expanding opportunities to connect physicians around the world utilizing various online platforms for neurosurgical education, such as live courses and webinars offered by the American Association of Neurological Surgeons.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown various e-learning and online learning tools that are effective for teaching and learning in the fields of health profession, including dentistry [2][3][4][5][6]. The knowledge gain and performance of the students as a result of E-learning were shown to be equivalent to that of face to face methods [7][8]. Blended learning is mainly defined as the integration of classroom and distance learning to facilitate an independent, interactive and collaborative learning among students.…”
Section: Introductionmentioning
confidence: 99%